For the family, $f_\theta(x)=\frac{e^{-(x-\theta)}}{1+e^{-(x-\theta)})^2}$, compute the fisher information, is it an exponential family, $x\in \mathbb{R},\theta \in \mathbb{R}$?

I computed the fisher information as $I(\theta)=E[(\frac{\partial log f_\theta(x)}{\partial\theta})^2]$

$\frac{\partial}{\partial\theta}lnf_\theta(x)=\frac{\partial}{\partial\theta}\ln\frac{e^{-(x-\theta)}}{(1+e^{-(x-\theta)})^2}=\frac{\partial}{\partial\theta}[\ln e^{-(x-\theta)}-\ln(1+e^{-x_\theta)})^2]=1-2\frac{1}{1+e^{-(x-\theta)}}\cdot e^{-(x-\theta)}$

Then $(1-2\frac{1}{1+e^{-(x-\theta)}}\cdot e^{-(x-\theta)})^2=1-4\frac{1}{1+e^{-(x-\theta)}}\cdot e^{-(x-\theta)}+\frac{e^{-2(x-\theta)}}{(1+e^{-(x-\theta)})^2}$

Then $E(1-4\frac{1}{1+e^{-(x-\theta)}}\cdot e^{-(x-\theta)}+\frac{e^{-2(x-\theta)}}{(1+e^{-(x-\theta)})^2})=1-4e^\theta E(\frac{e^{-x}}{1+e^\theta e^{-x}})+e^{2\theta}E(\frac{e^{-2x}}{1+e^{-(x-\theta)})^2})$

$E(\frac{e^{-x}}{1+e^\theta e^{-x}})=E(\frac{1}{\frac{1}{e^{-x}}+e^{\theta}})=\int_\mathbb{R}\frac{e^{-(x-\theta)}}{1+e^{-(x-\theta)})^2}\cdot\frac{1}{\frac{1}{e^{-x}}+e^{\theta}} dx$

So my issue now is I don't feel I can compute this integral, so maybe I've made a mistake in computing this somewhere.

For showing whether it is or isn't an exponential family, I believe it is not, but I'm not sure how to prove something is not an exponential family, only how to show it is.

My definition of exponential family is:

if $f_\theta(x)=h(x)e^{\sum_{i=1}^k c_i(\theta)T_i(x)-d(\theta)}$ then $f_\theta(x)$ is a k-parameter exponential family.

  • 2
    $\begingroup$ Use the alternative formula $I(\theta)=-E_{\theta}\left[\frac{\partial^2}{\partial\theta^2}\ln f_{\theta}(X)\right]$. $\endgroup$ Mar 14, 2022 at 19:22

1 Answer 1


It's good advice to switch to an alternative definition of Fisher's information if one of them takes you to a dead end to no avail. Observe that $$ \frac{d^2\ell}{d\theta^2} = -\frac{2e^{-(x-\theta)}}{(1+e^{-(x-\theta)})^2}. $$ Therefore, $$ \begin{align} I(\theta) &= -E\left(\frac{d^2\ell}{d\theta^2}\right) = 2\int_{-\infty}^{-\infty}\frac{e^{-(x-\theta)}}{(1+e^{-(x-\theta)})^2}\frac{e^{-(x-\theta)}}{(1+e^{-(x-\theta)})^2}\,dx\\ &= 2\int_{-\infty}^{\infty}\frac{e^{-2(x-\theta)}}{(1+e^{-(x-\theta)})^4}\,dx \end{align}. $$ Consider the transformation $y = \frac{e^{-(x-\theta)}}{1+e^{-(x-\theta)}}$ whose Jacobian is $dx = \frac{1}{(y-1)y}\,dy$. Note that $y\to 0$ as $x\to\infty$ and $y\to 1$ as $x\to-\infty$. Therefore, $$ \int_{-\infty}^{\infty}\frac{e^{-2(x-\theta)}}{(1+e^{-(x-\theta)})^4}\,dx = -\int_1^0 \frac{y^2(1-y)^2}{y(1-y)}\,dy=\int_0^1 y(1-y)\,dy = B(2,2), $$ where $B(a,b)$ is the beta function. Using the relationship between the beta function and the gamma function, $B(2,2) = \frac{\Gamma(2)\Gamma(2)}{\Gamma(4)} = \frac{1}{6}$. Therefore, $I(\theta) = \frac{1}{3}$.

Now, does the logistic distribution in your question belong to an exponential family? No, because the density cannot be represented as $h(x)\exp\{\eta(\theta)T(x)-A(\theta) \}$. Observe that the density $e^{-x}\exp\left[-2\log\{1+\exp(-(x-\theta))\} + \theta \right]$ is impossible to be rewritten in terms of the product of $\eta(\theta)T(x)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.